"Um buraco no céu de papel": o moderno na dramaturgia de Luigi Pirandello - Nosella, Berilo Luigi Deiró (2007)
This master degree main objective is the analysis and the study of the dramatical workmanship composition Six Personages in Search of an Author , witch is studied here as Seis Personagens em Busca de um Autor by Luigi Pirandello (1867-1936), staged for the first time in 1921, in Rome / Italy, reaching success in the entire world and deeply influencing the art of the teatral representation of the century XX. The objectives of the research send to analyze the modern elements gifts in the text Six Personages in Search of an Author and to the verification of the specific items on this modern pirandellian text in debate with modernity and contemporality. Basically, here, the analysis if guideline in the reflection on the existence of a tension between tradition and renewal, characteristic of the modernity in general way and specific way of the workmanship of Pirandello. It is treated, therefore, of formal examining the renewal as crisis of the tradition while factor of revelation and denudation as crisis of the modern world that is present like a mean form in the workmanship of Pirandello and in the Modern Drama . The literary analysis of the pirandellian text was based, initially, in the theoretical debate on the question of the literary sorts for the definition of the concept of Modern Drama . For this issue, this thought followed a line that begins with Hegel, goes to Georg Lukács and finishes with Peter Szondi. Advancing in this way, it was turned back to the proper theoretical texts of Pirandello, mainly O Humorismo , wrote in 1903, that involves the modernity of the drama and how it would be articulated, later, in an artistic form. A critical historical pillar helped to support the recital of this work that had as purpose understand and context this workmanship of Pirandello in its time and the present time. It was established, a parallel between two authors: the Italian, contemporary Pirandello, Antonio Gramsci and the german, Walter Benjamin. This debate in allowed in such a way to invest them in the analysis of the tension between form and content, renewing the art of drama of Pirandello culturally (as content) and the respective esthetic way (as form)